Nigerian stakeholders’ perceptions of a pilot tier accreditation system for Patent and Proprietary Medicine Vendors to expand access to family planning services - Funmilola M. OlaOlorun; Aparna Jain; Emily Olalere; Ene Daniel-Ebune; Kayode Afolabi; Emeka Okafor; Sara Chace Dwyer; Osimhen Ubuane; Toyin O. Akomolafe; Sikiru Baruwa (BMC Health Services Research, 2022)
Abstract Background Community Pharmacists (CPs) and Patent and Proprietary Medicine Vendors (PPMVs) are often the first point of care for many Nigerians, and when sufficiently trained, they contribute to the expansion of family planning services. Nigeria’s task shifting policy and existing regulatory and licensing bodies provide the enabling environment for PPMVs to be stratified and trained. This study explored the perceptions of stakeholders toward the pilot three-tier accreditation system instituted by the Pharmacists Council of Nigeria with support from the IntegratE project. Methods Two rounds of qualitative phone interviews were conducted among stakeholders in Kaduna and Lagos states in 2020 and 2021. In addition, there were two rounds of phone interviews with CPs and PPMVs (program recipients) from Lagos and Kaduna states. All participants were purposively selected, based on their involvement in the IntegratE project activities. Interviews were recorded, transcribed, and coded using Atlas.ti software. Thematic analysis was conducted. Results Fifteen stakeholders and 28 program recipients and 12 stakeholders and 30 program recipients were interviewed during the first and second rounds of data collection respectively. The data are presented around three main themes: 1) the pilot three-tier accreditation system; 2) enabling environment; and 3) implementation challenges. The accreditation system that allows for the stratification and training of PPMVs to provide family planning services was perceived in a positive light by majority of participants. The integrated supportive supervision team that included representation from the licensing and regulatory body was seen as a strength. However, it was noted that the licensing process needs to be more effective. Implementation challenges that need to be addressed prior to scale up include bottlenecks in licensing procedures and the deep-rooted mistrust between CPs and PPMVs. Conclusion Scale up of the three-tier accreditation system has the potential to expand access to family planning services in Nigeria. In other resource-poor settings where human resources for health are in short supply and where drug shops are ubiquitous, identifying drug shop owners, training them to offer a range of family planning services, and providing the enabling environment for them to function may help to improve access to family planning services.